Considering human interference to prioritize spatial conservation in a transboundary river basin using zonation - Meng Yuan; Lan Li; Hangnan Yu; Jiapeng Xiong; Jiangtao Yu (Scientific Reports)
Abstract Previous studies on priority conservation areas were more focused on ecological elements with less attention to human interference, this study intends to integrate human interference for spatial conservation prioritization (SCP) using Zonation software in the Wusuli River Basin (WRB; China–Russia). Ecosystem services, landscape connectivity, and human interference using the InVEST model, Conefor, and human footprint index along with the human interference index were integrated into Zonation5. The results indicated that the mean ecosystem services of the Wusuli River basin was 0.66, with higher value in Russia (0.75) than in China (0.49). Landscape connectivity was higher in eastern part (Russia), lower in western part (China), and moderate near the boundary. Condition, represented as the inverse of the human interference, averaged 0.49, with Russia achieving a higher value (0.53) than China (0.41). Priority areas were classified into five levels, with all the highest-priority areas located in Russia (31% of its area and 21% of the basin), while over 95% of the lowest-priority areas were in China (55% of its area and 20% of the basin). This study evaluates the conservation priority of WRB at the basin-wide scale from a multi-dimensional perspective, providing a basis for transboundary cooperative management.